2013
DOI: 10.1007/s11136-013-0386-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, human insecurity, and distress among Palestinians in the Gaza Strip before and after the Winter 2008–2009 Israeli war

Abstract: Purpose This study investigates changes in the quality of life (QoL) of Gaza Palestinians before and after the Israeli winter 2008–2009 war using the World Health Organization’s WHOQOL-Bref; the extent to which this instrument adequately measures changing situations; and its responsiveness to locally developed human insecurity and distress measures appropriate for context. Methods Ordinary least squares regression analysis was performed to detect how demographic and socioeconomic variables usually associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…52 It is interesting to note that a comparison of Gazans' QOL before and after the winter 2008-9 attack revealed that the standardized WHOQOL-BREF instrument could not detect significant changes in QOL scores. 53 In contrast, our locally developed measures of human insecurity and distress detected important increases in these two measures of suffering and reported health before and after the war, confirming the need to supplement or replace standardized international instruments with context-specific measures. This study also confirmed the importance of introducing a political domain into QOL instruments, that is, uncovering the political determinants of health.…”
Section: Developing New Measuresmentioning
confidence: 69%
“…52 It is interesting to note that a comparison of Gazans' QOL before and after the winter 2008-9 attack revealed that the standardized WHOQOL-BREF instrument could not detect significant changes in QOL scores. 53 In contrast, our locally developed measures of human insecurity and distress detected important increases in these two measures of suffering and reported health before and after the war, confirming the need to supplement or replace standardized international instruments with context-specific measures. This study also confirmed the importance of introducing a political domain into QOL instruments, that is, uncovering the political determinants of health.…”
Section: Developing New Measuresmentioning
confidence: 69%
“…Every dimension of daily life reminds Palestinians that they cannot control their own destiny. Lack of freedom and security, impossibility to access clean water and electricity or a decent educational and health system, unemployment, systematic harassment and violence, inability to move and leave the strip, contribute to an increasing sense of hopelessness and impotence (see Hammoudeh, Hogan, & Giacaman, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although Palestinians continue to be among the besteducated peoples in war and poverty affected zones (Høigilt, 2013;Nasser, Berlin, & Wong, 2011), the ongoing disruption of general economic, environmental, health, and living conditions also affects the education domain, contributing to further undermining opportunities for improvements in subjective well-being and familial QoL (Batniji, 2013;Hammoudeh, Hogan, & Giacaman, 2013). Families are forced into a paradox: on the one hand, they identify education as the one of the few opportunities for their children to cope with adversity and daily suffering; on the other, they see excellent educational opportunities as an extremely remote prospect for the children of Gaza (Khamis, 2013).…”
Section: Resultsmentioning
confidence: 99%